2021
DOI: 10.3389/fped.2021.756217
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Serum Vitamin A Levels and Recurrent Respiratory Tract Infections in Children

Abstract: To evaluate the association between serum vitamin A levels and the prevalence of recurrent respiratory tract infections (RRTIs) in children and adolescents and to provide evidence that would help decrease the prevalence of respiratory tract infections (RTIs) in children. This cross-sectional study included 8034 children and adolescents in Beijing aged 6 months to 17 years. RRTI and RTI symptoms were diagnosed according to the Clinical Concept and Management of Recurrent Respiratory Tract Infections in Children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
1
5
0
3
Order By: Relevance
“…Moreover, the results of this study showed that the proportions of premature infants, low body weight infants, special physique, hospitalization history, hypocalcemia, living in a bungalow, and daily outdoor activities less than 30 minutes in the case group were higher than those in the control group, which was in line with the prior scholars 8,9 who argued that children of different ages with recurrent respiratory tract infections are directly affected by the deficiencies of vitamins A, D and E, with those aged 0 to 1 most likely to suffer from deficiencies of there vitamins. The main risk factors for children with recurrent respiratory tract infections are lack of vitamins A, D and E, hypocalcemia, special physique, hospitalization history, living in a bungalow, and daily activity time of less than half an hour.…”
Section: Discussionsupporting
confidence: 84%
“…Moreover, the results of this study showed that the proportions of premature infants, low body weight infants, special physique, hospitalization history, hypocalcemia, living in a bungalow, and daily outdoor activities less than 30 minutes in the case group were higher than those in the control group, which was in line with the prior scholars 8,9 who argued that children of different ages with recurrent respiratory tract infections are directly affected by the deficiencies of vitamins A, D and E, with those aged 0 to 1 most likely to suffer from deficiencies of there vitamins. The main risk factors for children with recurrent respiratory tract infections are lack of vitamins A, D and E, hypocalcemia, special physique, hospitalization history, living in a bungalow, and daily activity time of less than half an hour.…”
Section: Discussionsupporting
confidence: 84%
“…Table 3 shows that the classification of vitamin A deficiency differed in some studies, Julien et al [ 30 ], Moreira et al [ 25 ] and Wang et al [ 35 ], categorized subclinical and clinical vitamin A deficiency serum retinol levels below <0.7 μmol/L and 0.35 μmol/L, respectively. Kjolhede et al [ 24 ], Nacul et al [ 31 , 32 ], Zuo et al [ 34 ], Kuti et al [ 36 ], and Li et al [ 37 ], classified vitamin A deficiency values below <0.7 μmol/L without categorizing it into subclinical or clinical deficiency, as well as Silva et al [ 33 ], who used another cutoff point to classify the inadequate serum retinol level (<1.05 μmol/L).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, micronutrient imbalance is associated with the risk of complicated respiratory tract infections, as has been reported for vitamins A, D, E, and C and the trace elements zinc and magnesium [12][13][14][15][16][17][18][19][20]; therefore, their supplementation improves the effector function of the immune system, as has been excellently reviewed elsewhere [21,22]. Here we will focus on how those micronutrients mentioned above, in which deficiency or supplementation impacts immune function, participate at the molecular level in each step of the immune response against respiratory viruses.…”
Section: Introductionmentioning
confidence: 81%